Improvement of the efficiency and stability of inkjet‐printed green quantum dot light‐emitting diodes by controlling the extra shell of quantum dot. Issue 7 (1st March 2022) - Jia, Siqi; Liu, Pai; Ma, Jingrui; Qu, Xiangwei; Tang, Haodong; Li, Depeng; Tang, Jing; Wang, Zhaojin; Li, Guangyu; Wang, Kai; Yang, Xiaochuan; Xu, Wenwei; et al.
Abstract: Inkjet printing as an effective patterning deposition technology is very suitable for the fabrication of quantum dot light‐emitting diodes in next‐generation displays. However, there are still many challenges in achieving high efficiency and stability of the printed device. Herein, we reported the inkjet‐printed quantum dot light‐emitting diodes with an external quantum efficiency of over 20% and half lifetime at 1000 cd/m 2 of 27, 000 h for the first time. Such excellent performance is owing to the successfully optimal thickness (seven monolayers) of the extra ZnS shell, which improves the balance of the carries injection to suppress the nonradiative process for inkjet‐printed devices. Overall, this performance from inkjet‐printed quantum dot light‐emitting diodes accelerates the printed device to meet the requirements of practical display and lighting applications. Abstract : The extra ZnS shell optimal thickness (seven monolayers) of quantum dot is applied to improve the balance of the carries injection to suppress the nonradiative process for inkjet‐printed devices. A high efficiency and stable inkjet‐printed quantum dot light‐emitting diode is also fabricated.